2022
DOI: 10.1051/ctv/ctv202237011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abscisic acid,Ascophyllum nodosumandAloe veraon the phenolic composition and color of grape berry and wine of 'Cabernet Sauvignon' variety

Abstract: In viticulture, various techniques can be used to improve productivity, tolerance to biotic or abiotic stress, the quality of grapes and wines such as the use of plant regulators and biostimulants. Thus, the objective of this work was to evaluate the effect of application of abscisic acid (S-ABA), Ascophyllum nodosum (A. nodosum) seaweed extract and Aloe vera (A. vera) gel on phenolic composition and chromatic characteristics of grapes from the 'Cabernet Sauvignon' variety. The experiment was conducted in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Aloe vera leaves contain bioactive compounds such as antioxidants. Application of Aloe vera was used on fruit trees to improve grape productivity and quality (Pessenti et al, 2022) or two extend the shelf life of grape under storage (Farahi, 2015 andAlberio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe vera leaves contain bioactive compounds such as antioxidants. Application of Aloe vera was used on fruit trees to improve grape productivity and quality (Pessenti et al, 2022) or two extend the shelf life of grape under storage (Farahi, 2015 andAlberio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Seaweed extracts are used in grapevines for enhancing vine growth and yield of grape cultivars. Many investigators found that, the seaweed extract stimulated the vegetative growth and increased yield with better berry quality (Norrie and Keathley, 2005;Kok et al, 2010;Ahmed et al, 2013;Carvalho et al, 2019;Salvi et al, 2019;Taskos et al, 2019 andPessenti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chile was the first country to register and commercially use s-ABA between 2009(Valent BioSciences Co., 2009. ProTone ® also improves fruit quality, for example, in grapes, it enhances the anthocyanins and total polyphenol contents (Pessenti et al, 2022). In Australia, six case studies on ProTone ® , involving five grape vine varieties, demonstrated yield benefit and higher market prices (Sumitomo Chemical Australia Pty Ltd, 2019).…”
Section: In Fruit and Nut Horticulturementioning
confidence: 99%
“…Aggrandized the total polyphenol content, total anthocyanins amount, and PAL in the berry skin. [194] Ascophyllum nodosum can be a sustainable management tool to lessen the short-period shock of severe temperatures and strong light irradiance in grapevines; in fact, it was found that it was able to encourage a prompt photosynthetic recovery after drought stress [184]. In addition to this, numerous studies have highlighted its positive effect on the phenolic composition of berries [189,192,194].…”
Section: Ascophyllum Nodosum Sangiovesementioning
confidence: 99%